2001
DOI: 10.1002/1098-2825(2001)15:1<1::aid-jcla1>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyurea-induced oxidative damage of normal and sickle cell hemoglobins in vitro: Amelioration by radical scavengers

Abstract: Hydroxyurea (HU) induces fetal hemoglobin (Hb F) production in patients with sickle cell anemia. The therapeutic dosage of HU used for Hb F induction often elicits myelosuppression, which becomes its major associated complication. We examined the effect of HU on hemoglobin modulation and the role of radical scavengers on these induced changes. In vitro exposure of human blood to various concentrations of HU at predetermined time intervals induced a progressive dose‐dependent oxidation (MetHb formation) of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
12
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 20 publications
5
12
0
Order By: Relevance
“…An increase in these enzymes suggests an adaptive response of the RBCs to oxidative damage. These findings are in agreement with the findings of Iyamu et al (13) that HU-induced oxidative damage of Hb can be ameliorated by radical scavengers. Similarly, Eskenazi et al (14) demonstrated that resistance to exogenous H 2 O 2 after HU treatment in B16 melanoma cells was accompanied by an increase in free radical scavengers like glutathione reductase, glutathione peroxidase and catalase activities.…”
Section: Discussionsupporting
confidence: 93%
“…An increase in these enzymes suggests an adaptive response of the RBCs to oxidative damage. These findings are in agreement with the findings of Iyamu et al (13) that HU-induced oxidative damage of Hb can be ameliorated by radical scavengers. Similarly, Eskenazi et al (14) demonstrated that resistance to exogenous H 2 O 2 after HU treatment in B16 melanoma cells was accompanied by an increase in free radical scavengers like glutathione reductase, glutathione peroxidase and catalase activities.…”
Section: Discussionsupporting
confidence: 93%
“…Further investigation to assess the post-translational modification of catalase using 2D quantitative western blotting showed a twofold increase in tyrosine phosphorylation with hydroxyurea exposure. This observation is consistent with prior studies that showed phosphorylation of catalase by tyrosine kinases in response to oxidative stress, increasing catalase activity at a post-translational level [4648]. It is remarkable that this set of in vitro hydroxyurea experiments yielded alterations in protein abundance, since the principal effects of hydroxyurea have previously been attributed to alterations in transcriptional regulation that are not possible in enucleated mature RBCs.…”
Section: Rbc Membrane Proteomics In Scdsupporting
confidence: 91%
“…Hydroxyurea also induces both hemoglobin denaturation and oxidative damage within red blood cells [97][98][99][100]. Further EPR examination of the reaction of oxyhemoglobin and hydroxyurea reveals the formation of three other paramagnetic species in addition to methemoglobin [101].…”
Section: Reactions With Heme Proteinsmentioning
confidence: 97%